Safety and effectiveness of all-oral and injectable-containing, bedaquiline-based long treatment regimen for pre-XDR tuberculosis in Vietnam - Nguyen, Thi Mai Phuong; Nguyen, Binh Hoa; Hoang, Thi Thanh Thuy; Nguyen, Hoang Anh; Vu, Dinh Hoa; Nguyen, Mai Hoa; Nguyen, Bao Ngoc; Decroo, Tom; Nguyen, Viet Nhung (Frontiers in Pharmacology, 2022)
Background: The World health organization (WHO) recently recommended standardized all-oral shorter regimens for rifampicin resistant Tuberculosis (RR-TB). For highly resistant TB patients such as pre-XDR-TB, the 6-9-month bedaquiline (BDQ)-based regimens or BDQ-based long regimens are recommended. The role of second-line injectable (SLI) drugs in the treatment of drug resistant TB is restricted because of safety concerns. Nevertheless, it is not well-known how all-oral long regimens (BDQ-long) perform compared to SLI-containing long regimens (BDQ/SLI-long) in terms of safety and effectiveness among patients with highly resistant TB. Method: A prospective observational cohort of patients with RR-TB additionally resistant to FQ and/or SLI, treated with either BDQ-long or BDQ/SLI-long regimens according to the guidance of the National Tuberculosis Program of Vietnam, enrolled between December 2015 and June 2017. Results: Of 99 patients enrolled, 42 (42%) patients were treated with BDQ-long and 57 (57%) with BDQ/SLI-long. More than 85% of patients were previously exposed to both FQ and SLI. FQ and SLI resistance were confirmed in 28 (67%) and 41 (98%) in the BDQ-long cohort and 48 (84%) and 17 (30%) in the BDQ/SLI-long cohort, respectively. Treatment success was achieved among 29 (69%) and 46 (81%) patients on the BDQ-long and BDQ/SLI-long regimen, respectively (p=0.2). For both regimens, median time to first smear/culture sputum conversion was 2 months. All patients experienced at least one adverse event (AE) and 85% of them had at least one severe AEs (grade 3-4). The median time to a first severe AE was two months. Among patients treated with BDQ-long a higher proportion of patients had three QT-prolonging drugs in the regimen (26.2% versus 7.0%; p=0.009). The severe prolonged QTcF was observed in 22 (52.4%) and 22 (38.6%) patients on BDQ-long and BDQ/SLI-long, respectively. Overall, 30 (30%) patients had to either temporary or permanently discontinued or more TB drugs due to AEs. Conclusion: Treatment success was similar for both all-oral and SLI-containing BDQ-based long regimens in highly resistant TB patients. Both regimens had a similar high frequency of AEs. For both BDQ-long and BDQ/SLI-long regimens active AEs monitoring is essential.